(untitled) (Research, Society and Development, 2022)
Coffin-Siris syndrome is a genetic condition caused by mutations in genes that are responsible for encoding components of the BAF complex, causing hypoplasia or aplasia of the fifth finger phalanx, coarse facial appearance, developmental delay, intellectual retardation, sparse hair, hypotonia, cardiac and brain abnormalities, among other characteristics. In this sense, the objective of this article is to present a case report on the progression of the diagnosis of Coffin-Siris Syndrome (CSS), where the initial signs and symptoms can be imprecise to make the diagnosis, being necessary to resort to genetic tests for the diagnosis. confirmation of the syndrome.